(untitled) (International Journal of Engineering and Computer Science, 2014)
Personal data stored in cloud may contain account numbers or passwords or notes or any other important information that could be used and misused by a hacker, a competitor, or a court of law. These data are cached, copied, and used by Cloud Service Providers (CSPs), often without users authorization and control. SeDas mainly aims at protecting the user data’s privacy. All these data and their copies become destructed or unreadable after a user-specified time, without any user intervention. In addition to that the decryption key will be destroyed after the user-specified time. The presence of SeDas, a system that meets this challenge through a novel integration of cryptographic techniques with active storage techniques based on T10 OSD (Object Storage Device) standard provides a recovery mechanism to the legitimate users to obtain their data back by requesting to the cloud admin. A new key is be sent to the legitimate user either to the Email or to Mobile using this key he has to login to the SeDas platform to get back their data. So this approach is more efficient to use and possible to achieve all the privacy preserving goals.